Does space matter? The case of the housing expenditure cap - Yifan Gong; Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2023)
In our evaluation of the housing expenditure share cap, a macroprudential policy, we discover the importance of modeling space. The spatial considerations allow households to sort into segmented housing markets based on income. Our model generates the observed negative relationship between housing expenditure share and income. More importantly, the cap policy causes a more considerable reduction in housing costs for low-income families than for high-income families in a spatial model. Depending on the assumption of households' preference, this mechanism leads to a minor increase or even a modest decrease in welfare inequality in a spatial model than in a spaceless model.
Keywords: D04; R20; R30; 330; housing expenditure share; monocentric model of a city; spatialsorting; welfare inequality